Youth on the Frontlines: Preventing Human Rights Abuses in Violent Contexts, A Case Study of LUCHA in the DR of Congo. (2nd May 2022) - Cirhigiri, Christian
ABSTRACT ∞ : Increasingly, transitional justice (TJ) mechanisms are implemented in contexts of ongoing violence where youth are often perceived as victims or perpetrators of human rights violations. This reductionist conceptualization of youth is problematic for understanding the diverse identities of youth in contexts where large-scale human rights violations occur. It also obscures the positive roles of youth as non-State actors in advancing human rights accountability and preventing the recurrence of specific human rights violations. This article explores how youth participation in LUCHA—a countrywide youth movement born from Goma (North Kivu) that advocates for greater political and civic involvement of Congolese—influences youth understandings of justice and contributes to the non-recurrence of specific human rights violations. Using collective participation as a conceptual lens and semi-structured interviews and focus groups conducted in 2015 and 2021 with LUCHA activists, the article contends that overemphasizing State actors eclipses non-State actors' roles—including youth-led peace and justice initiatives in areas where State actors are inexistent or have weakened legitimacy. The article's central claim is that ignoring the nexus between youth participation and justice understandings, particularly in contexts of ongoing violence, limits TJ's full potential to unfold in these contexts. By zooming in on the TJ pillar of Guarantees of Non Recurrence (GoNR), the article is an invitation to further interrogate youth's roles in TJ contexts and expand the field's toolkit to accommodate their unique contributions.